2022
DOI: 10.1002/pc.27210
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing pseudo‐ductility in carbon/glass fiber hybrid composites manufactured using infusible thermoplastic Elium® resin

Abstract: In this study, two different type of glass and carbon fiber hybrid laminates were manufactured using a low-viscosity thermoplastic resin that is, Elium ® .A detailed microstructure visualization study was conducted using X-ray computed tomography (XCT) analysis. The viscoelastic properties were examined through dynamic mechanical analysis. The mechanical performance was investigated through flexural and tensile tests along with a fractographic study using optical and scanning electron microscopy. The XCT analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Apart from that, the microscopic failure comprised delamination, fiber pull out, fiber cracking, and resin damage. Numerous studies in the literature have observed similar failure modes in CFRP composite specimens [ 42 , 43 , 44 , 45 ]. The results also showed a strong interface between the fibers and the thermosetting matrix, which was primarily due to the high surface roughness of the carbon fibers.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Apart from that, the microscopic failure comprised delamination, fiber pull out, fiber cracking, and resin damage. Numerous studies in the literature have observed similar failure modes in CFRP composite specimens [ 42 , 43 , 44 , 45 ]. The results also showed a strong interface between the fibers and the thermosetting matrix, which was primarily due to the high surface roughness of the carbon fibers.…”
Section: Resultsmentioning
confidence: 86%
“…Along with this, the fibers were also pulled out and fractured upon the complete failure of the scarf joints, as the scarf geometry was pulled out due to complete delamination. The carbon fibers exhibited the commonly observed brittle fracture mode, especially along the edges of the scarf joints [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating fibers into polymers has been widely accepted as a facile strategy for strengthening the polymer matrix, including the mechanical behaviors, [1][2][3][4] rheological applications, 5 thermal stability, 6,7 damping properties, [8][9][10] corrosion resistance, 11,12 and flame retardation. [13][14][15] The fiber/matrix interphase has played significant roles in transmitting external stress from resin matrix to high strength fibers [16][17][18][19] since the polymer matrix suffers from external stress.…”
Section: Introductionmentioning
confidence: 99%
“…It offers enhanced stiffness and improved toughness comparable to its thermoset counterparts. 1,7,8 Recently, significant attempts have been noted in the literature scrutinizing the mechanical attributes of this novel elium resin-based composites consisting of different fiber reinforcements. For instance, Pinto et al reported that glass/carbon fiber reinforced composites (FRCs) produced with elium and epoxy resin exhibit similar behavior for using the same fiber reinforcement; also, composites with elium matrix had shown less impact damage.…”
Section: Introductionmentioning
confidence: 99%